Melatonin ameliorates oxidative stress-mediated injuries through induction of HO-1 and restores autophagic flux in dry eye. (April 2021) - Wang, Bowen; Zuo, Xin; Peng, Lulu; Wang, Xiaoran; Zeng, Hao; Zhong, Jing; Li, Saiqun; Xiao, Yichen; Wang, Li; Ouyang, Hong; Yuan, Jin
Abstract: This study aimed to investigate the protective effect of melatonin on the corneal epithelium in dry eye disease(DED) and explore its underlying mechanism. Human corneal epithelial(HCE) cells was exposure to t-butylhydroperoxide(tBH), C57BL/6 mice were injected of subcutaneous scopolamine to imitate DED. Melatonin was used both in vivo and in vitro. Cell viability was detected by Cell Counting Kit-8 assay and Lactate Dehydrogenase Leakage. The change of cellular reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP), and apoptosis was analyzed by flow cytometry. Western blot assays and immunofluorescence were carried out to measure protein changes. mRNA expression was investigated by RNA sequencing (RNA-Seq) and quantitative real-time PCR. The change of autophagic flux were observed through mCherry-GFP-LC3 transfection and electron microscopy(TEM). Clinical parameters of corneal epithelium defects, conjunctival goblet cells, tear volume, and level of ocular surface inflammation was recorded. Melatonin was able to reduce excessive ROS production and maintain mitochondrial function. TEM assay found melatonin rescued impaired autophagic flux under tBH. Moreover, melatonin significantly preserved cell viability, abolished LDH release, and decreased apoptosis. RNA-Seq indicated that melatonin greatly activating hemeoxygenase-1 (HO-1) expression. Interestingly, HO-1 ablation largely attenuated its protective effects. Besides, in dry eye mouse model, intraperitoneal injection of melatonin showed greatly improved clinical parameters, inhibited activated NLRP3 inflammation cascade, and increased density of goblet cells and tear volume. Thus, melatonin protects corneal epithelial cells from oxidative damage, maintain normal level of autophagy, and reduce inflammation via trigging HO-1 expression in DED. Highlights: Melatonin can protect corneal epithelial cell viability and inhibit apoptosis from oxidative damage in vitro. Melatonin maintains healthy autophagic flux, reduces ROS level via trigging HO-1 expression. melatonin in vivo greatly protected ocular surface and inhibited inflammation activation.